Mutual influence of morality and religion - Ybyray, N.Sh. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The article was written in the scope of the topic of the dissertation research “The problem of relationship of morality and religion in Kazakh philosophy”. The article examines the intricate relationship between morality and religion, exploring their historical, philosophical, and cultural intersections. It highlights the evolution of moral norms as both independent of and intertwined with religious ideologies. These secular approaches frequently prioritize practical outcomes, emphasizing efficiency and overall benefits. However, individualistic and utilitarian perspectives can sometimes conflict with deeper, more intrinsic moral values associated with religion. As a result, whereas secular morality can foster social cohesion and progress, it does not always align with deeper moral principles that surpass purely practical considerations. This perspective suggests that morality is a product of social and historical evolution rather than being dictated by practical reasons. Although moral standards have traditionally been tied to religious consciousness, their modern humanistic reinterpretation places greater emphasis on their genetical connection with sources and process of emancipation of moral norms from religion, becoming secular morality as independent construction. The article ultimately discusses the question of the dependance and contextual nature of religion on morality and at the same time autonomous nature of moral obligations, underscoring the importance of situational ethics and human decision- making over rigid absolutes. In conclusion, it advocates viewing morality as an autonomous form of social awareness, fully capable of guiding humanity independent of religious influence.
Keywords: virtue; happiness; emancipation; moral values; secularization; culture; humanism; God; ethics